Technical perspective: WebAssembly: a quiet revolution of the web. - Møller, Anders (Communications of the ACM, 2018)
This article discusses the low-level computer programming language for software known as WebAssembly. The author comments on the use of WebAssembly to enable JavaScript engines on web browsers and describes the program's semantic design, which can function regardless of computer hardware or operating system.